UPAYA PENANGGULANGAN TINDAK PIDANA PENCURIAN TERNAK (STUDI KASUS DI POLSEK NEGARA) - Krisna Pandita Mahayana, Ida Bagus; Tjatrayasa, I Made; Wirasila, A. A. Ngurah (Kertha Wicara : Journal Ilmu Hukum, 2013)
Rampant theft of livestock thefts in the Negara city especially making peoplerestless. Perpetrators of theft of livestock is no longer an amateur thief, even a thief whois already a steal livestock specialist. Therefore, this paper will describe efforts tocombat the crime of theft of livestock and a contributing factor, especially in the regionNegara police station. Based on research results directly in Negara police station, thehigh cases of cattle theft that occurred in the area of Negara police station becausemany factors that cause. these factors are factors economy, intention and chancefactors, factors as easily be traded, the scene of factors, and the factors that have to beprofessional actors steal livestock specialist. With the number of factors in the region'slivestock theft Negara police station there should be overcome.reduction by Negarapolice station was established intelligence network, forming tring detectives, making acreative breakthrough "Jembrana eling", simakrama implement, carry out patrols andconduct dialogue sambang.
Keywords: Countermeasures, Theft, Livestock